0
$\begingroup$

This question already has an answer here:

Question

I got as far as distributing the summation across the Left Side so that I have:

$$ \sum_i y_i^2 - \sum_i 2 y_i \bar{y} + \sum_i \bar{y}^2 $$

Not sure where to go from there.

$\endgroup$

marked as duplicate by Xi'an, John, Silverfish, whuber Sep 26 '16 at 14:31

This question has been asked before and already has an answer. If those answers do not fully address your question, please ask a new question.

  • $\begingroup$ Please add the [self-study] tag & read its wiki. $\endgroup$ – Silverfish Sep 24 '16 at 21:50
1
$\begingroup$

A very common trick in these situations where you have an expression on the left and an expression on the right involving a term that doesn't appear on the left is to either add and subtract or multiply and divide by that term, depending on context. Here you can try

\begin{align} \sum_{i=1}^{n} (y_i - \bar{y})^2 &= \sum_{i=1}^{n} (y_i - \hat{y}_i + \hat{y}_i - \bar{y})^2 \\ &= \sum_{i=1}^{n} (y_i - \hat{y}_i)^2 + \sum_{i=1}^{n} (\hat{y}_i - \bar{y})^2 + 2 \sum_{i=1}^{n} (y_i - \hat{y}_i) (\hat{y}_i - \bar{y}) . \end{align}

Now we just need to show that the rightmost term equals zero. You should be able to convince yourself that $\sum_{i=1}^{n} (y_i - \hat{y}_i) = 0$ by plugging in the formula for $\hat{y}_i$ so we only need to prove that $\sum_{i=1}^{n} (y_i - \hat{y}_i) \hat{y}_i = 0$,

\begin{align} \sum_{i=1}^{n} (y_i - \hat{y}_i) \hat{y}_i &= \sum_{i=1}^{n} (y_i - \hat{y}_i) (\bar{y} - \hat{\beta}_1 \bar{x} + \hat{\beta}_1 x_i) \\ &= \hat{\beta}_1 \sum_{i=1}^{n} (y_i - \hat{y}_i) (x_i - \bar{x}) \end{align}

and the remaining steps can be found in my answer to this question: Proof that $\hat{\sigma}^2$ is an unbiased estimator of $\sigma^2$ in simple linear regression.

$\endgroup$
  • $\begingroup$ So, I followed your logic and got the first two parts of the right side. But I can't figure out how the rightmost term equals zero. I know that sum(yi-ybar)=0, but does the same principle apply for yhat? $\endgroup$ – Sohail Sep 25 '16 at 19:48
  • $\begingroup$ I actually had some typos in my original answer, sorry about that. Yes you should be able to show that $\sum_{i=1}^{n} (y_i - \hat{y}_i) = 0$. Anyways, I showed the rest of the steps from there. $\endgroup$ – dsaxton Sep 26 '16 at 0:57

Not the answer you're looking for? Browse other questions tagged or ask your own question.